Indications of Exploratory Laparotomy in Tertiary Care Centre of Eastern Nepal - Subedi, Shanti; Banerjee, Bashudev; Sharma, Anjana (Journal of Nobel Medical College, 2013)
Journal of Nobel Medical College Vol. 2, No.2 Issue 4 May-October 2013 Page 74-78 DOI: http://dx.doi.org/10.3126/jonmc.v2i2.8811